Anomalous transport behavior of La0.825Sr0.175MnO3-d polycrystalline samples below Curie temperature - Pogorilyi, A. N.; Belous, N. A.; Tovstolytkin, A. I.; Belous, A. G.; Yanchevski, O. Z. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The temperature (T) dependencies of resistivity (r0) and magnetoresistance (MR) in the range of 100-300K have been investigated in La0.825Sr0.175MnO3-d polycrystalline samples with different sintering temperatures TS(1300 C and 1360 C). Two peaks on the r0(T) curve were found in the sample with the lower value of TS. Inhomogeneity of the spin configuration and multiply-connectedness of ferromagnetic phase is believed to give rise to anomalous behavior of resistivity below the Curie temperature.